Hidradenitis suppurativa: Presenting at atypical sites - Sandhya Kumari; Mudita Gupta; Reena K Sharma; Lalita Negi (Wolters Kluwer Medknow Publications, 2018)
Hidradenitis suppurativa (HS) is a chronic inflammatory and debilitating disease of apocrine gland-rich areas. Characteristic bilateral involvement of the axilla, perineum, or inguinal folds is a hallmark feature of HS. Certain uncommon sites such as face, neck, jaw region, and legs, which are devoid of apocrine glands, are also involved in some cases. Here, we describe a case of HS involving uncommonly reported sites such as wrist, mid-back, and thigh at initial presentation which were misdiagnosed as scrofuloderma. She later had lesions on less common areas, such as buttocks, and the classical sites, such as groin and axilla, whence a final diagnosis of HS was made. The peculiarity of our case is the onset of disease from atypical sites which are devoid of apocrine glands and terminal hair follicles.